Tall Spindle – Apple orchard planting system for the future - Kumawat, K L; Mir, J I (Indian Horticulture, 2021)
The fruiting potential of the apple tree largely governed by its architecture, canopy density and photosynthetic efficiency. With the research advancement many orchard planting system have been developed in apple to optimize production and quality of produce.The Tall Spindle orchard planting system is new apple orchard plating system which is gaining popularity around the world and is ideally suitable for Indian condition particularly for the Kashmir region. This system utilizes the concept of optimum tree density planting with high quality feathered nursery tree and minimal pruning at planting to get high early yield and sustained mature yield of high quality fruits while reducing and simplifying mature tree pruning and other management costs. The system achieves high light interception by growing tree to a height of 90% of row spacing and good light distribution throughout the canopy by keeping the tree canopy thin. Moreover, this system also provides opportunity of partial mechanization of training, pruning, fruit thinning and harvesting using platforms.